The effect of spacing on incidental and deliberate learning of L2 collocations. (December 2021) - Macis, Marijana; Sonbul, Suhad; Alharbi, Rezan
Abstract: Previous studies investigating the effects of spacing on vocabulary learning have primarily focused on single words. There is limited research on how distributed practice affects the learning of the phrasal lexicon. The present study addresses this gap by focusing on collocations. In a pretest-treatment-delayed-posttest design, two controlled quasi-experiments (N = 55 and N = 50) were conducted in order to evaluate two spacing schedules, spaced versus massed . The participants learned 25 adjective-noun collocations either incidentally (Experiment 1) or deliberately (Experiment 2). In each experiment, a control group was included. Participants' collocational gains were measured at a form-recall level of mastery three weeks after the treatment. Mixed-effects regression modelling results indicate that spacing had a significantly large effect on vocabulary gains in the deliberate learning condition and a small effect on gains in the incidental learning condition. Massing, on the other hand, appears to be more effective (with a medium effect) in incidental learning situations. Implications for pedagogy and materials design are followed by suggestions for future research.